"What About the Rest of Us?" An Overview of LGBT Poverty Issues and a Call to Action. Issue 3 (1st September 2016) - DeFillippis, Joseph Nicholas
ABSTRACT: In this article, I argue that, despite the myth of gay affluence, existing research is conclusive enough to claim that lesbian, gay, bisexual, and transgender (LGBT) adults are overall less financially secure than their heterosexual, cisgendered counterparts. I demonstrate that LGBT poverty is a broad social issue that can no longer be viewed as affecting only specific subpopulations of LGBT communities. I argue that the social work profession and the LGBT movement need to recognize LGBT poverty as a social issue. I then present a call to action for social work practitioners, researchers and LGBT organizations.